Dye synthesis in the Pechmann reaction: catalytic behaviour of samarium oxide nanoparticles studied using single molecule fluorescence microscopy. Issue 2 (24th November 2015) - Hodgson, Gregory K.; Impellizzeri, Stefania; Scaiano, Juan C.
Abstract : Single molecule fluorescence microscopy has shown that samarium oxide nanoparticles efficiently catalyze the formation of coumarin 153 via a semi-heterogeneous catalytic process. Abstract : Photochemically prepared samarium oxide nanoparticles (Sm2 O3 NP) efficiently catalyze the formation of coumarin 153 via the Pechmann trans-esterification and condensation process. The formation of the fluorescent coumarin allowed the catalytic process to be monitored in real time at the single molecule level using Total Internal Reflection Fluorescence Microscopy (TIRFM). Benchtop experiments conducted in parallel demonstrated that the observed catalysis occurred in solution rather than by pure heterogeneous catalysis and is due to a mobile population of small Sm2 O3 NP released from a polydisperse original sample containing larger particles. TIRFM provided unique insights by demonstrating that catalysis by these smaller colloidal particles is in fact a surface process, while the larger particles are merely suppliers of the small catalytic nanostructures. We refer to this behaviour as a semi-heterogeneous catalytic system. This work showcases the opportunity that single molecule fluorescence techniques can offer in terms of understanding and ultimately improving benchtop and scaled-up synthesis. This specific example highlights the general applicability of this approach to the study of widely-utilized chemical reactions and lays the groundwork for researchers to adopt similar strategies in other systems.